Fate of natural organic matter and formation of disinfection by-products in a conventional water treatment plant - Abdel Halim, Noha Hesham (AUC Knowledge Fountain, 2014)
Elevated levels of disinfection by-products (DBPs), detected in Cairo residential water supply during the past decade, were the motivation to study the process of DBP formation at the water treatment plant (WTP) stage. It is hoped that an in-depth understanding of natural organic matter (NOM) characteristics and DBP formation/removal in an existing WTP will yield a baseline as well as insights for the development of optimum strategies for cost-effective reduction of potentially harmful drinking water compounds such as Trihalomethanes (THMs) and Haloacetic acid (HAAs). The objectives of this research were to: investigate the degree of removal of the various NOM fractions in conventional WTPs and identify the factors that may possibly enhance their removal; and investigate the levels of formed DBPs within conventional WTPs when pre-chlorination and post-chlorination are applied. Water samples were collected from El-Fustat WTP in Cairo from 4 different points along the treatment process and covering the four different seasons of a year. NOM was quantified by classical surrogate parameters such as total organic carbon (TOC), dissolved organic carbon (DOC), and ultraviolet absorbance (UVA254); and characterized more precisely according to its hydrophobic-hydrophilic properties using resin fractionation. THMs, HAAs and other water quality analyses were conducted for all collected samples. Measurements of NOM fractions following each treatment unit indicate that the hydrophobic fraction is significantly removed by the coagulation/flocculation/ sedimentation processes (56% to 13% in the various seasons) whereas the transphilic, and hydrophilic fractions were removed to much lower degree (51% to 10%) and (15% to 4%), respectively. The hydrophobic fraction had formed flocs with the added alum more than the other two fractions. No further removal of NOM takes place in rapid sand filtration or post-chlorination units. Although the THMs values recorded for the entire study were complying with the Egyptian guidelines, it is not guaranteed that tap concentrations will comply to the guidelines limits. This is because THM/THMFP does not exceed 39%, leaving room for 61% to be reacted in pipe lines and storage tanks until it reaches the customers taps. In addition, HAAs concentrations at the plant effluent were much higher than the regulating limits, alarming the WTP to exert more effort to reduce THMs, and HAAs values. On an attempt to identify the relative importance of NOM fractions in THMs formation, the measured values of the THMs were regressed to each NOM fraction and the coefficient of determination (R2) was calculated. Results showed that unlike hydrophobic fraction and transphilic fractions (R2 = 0.01, 0.14), respectively, hydrophilic NOM fractions are consistently most responsible for THM and HAAs production at the plant effluent (R2 = 0.77, 0.62. Although, hydrophilic fraction was the main contributor to THMs and HAAs formation in El-Fustat WTP; coagulation/flocculation and sedimentation could not successfully remove it during treatment. Accordingly, the processes of coagulation/flocculation/sedimentation/filtration are not guaranteed to be useful in decreasing the DBPs levels. El-Fustat WTP does not technically implement “Enhanced Coagulation"; however, initial results from this study shows that the hydrophillic DOC fraction is less likely to be removed during Enhanced Coagulation but the major DOC contributor to DBPs formation. Future work should test this hypothesis through a bigger and wider sample size. Free chlorine concentrations are responsible for the high THM levels at the plant effluent, which implies its responsibility on THMs formed in the plant and the formation potential in distribution pipelines. Therefore, reducing the chlorine doses as much as possible to reach zero free chlorine before post-chlorination and the minimum acceptable free chlorine residual for secondary disinfection is going to reduce the THMs and HAAs levels substantially.